EFEKTIVITAS PEMBERIAN GULA AREN (Arenga pinnta) TERHADAP GAMBARAN JUMLAH SEL RADANG DAN LUAS FIBROSIS PADA MIOKARDIUM TIKUS JANTAN GALUR WISTAR YANG DIINDUKSI ALOKSAN - Meilita Mutiara Hanifah, (2020)
Chronic hyperglycemia in Diabetes Mellitus can cause free radical formation and trigger oxidative stress, one of which is damage to the heart muscle. Palm sugar contains calcium and many antioxidant compounds as blood glucose-lowering agents, thereby reducing the production of oxidative stress. The aim of this research is to know the effectiveness of giving palm sugar (Arenga pinnata) towards the changes in myocardium histopathology of wistar rats induced by alloxan. The research design is true experimental. Samples of 25 male Wistar rats were divided into 5 groups with 6 male wistar rats in each group. The negative group, positive control were given alloxan, and 3 treatment groups. Induction of 120 mg/kgBB alloxan by giving palm sugar solution at a dose of 360 mg/day, and 720 mg/day. Intraperitoneal induction of alloxan, and periodic fasting blood glucose measurements, also palm sugar interventions for 38 days, were then surgically performed for making heart preparations with HE staining. The data were statistically tested using Kruskall Wallis test with P = 0.001 which indicates the effectiveness of palm sugar in improving the myocardium histopathology. The result of Mann Whitney test showed a dose of 180 mg/day was the most effective in decreasing blood glucose and improving the diabetic rat mycoardium histopathology (p = 0,008) and equivalent with a dose of 360 mg/day (p = 0,549).